FREEDOM OF RELIGION IN THE PRINCIPLES OF THE ISLAMIC NOMOKRASI - Astomo, Putra (Journal of Humanity, 2015)
Human thought about the country laws developed in various situations the history of human civilization. Although the concept of State law is regarded as a universal concept and are recognized by civilized nations, but at the level of implementation turns out to have a diverse character and traits. This happens because the influence of the historical situation in addition to the influence of the philosophy of the nation, schools of philosophy and the political ideology of a country. One of the substance of the State of law is the guarantee of the protection of human rights (human rights). Therefore, the context of the freedom of religion cannot be separated from the HAM as it is a human right that belongs to every citizen to embrace a religion according their respective beliefs. By understanding the existence of Nomokrasi Islam as the countrys law that put the norms of Islamic law (Sharia) in the Organization of the Government of a country, then the right of religious freedom also need to be protected